On the presence in Europe of two Illinoia aphids of North American origin (Homoptera, Aphididae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two aphids belonging to the genus Illinoia and native from the Nearctic Region (USA) are recorded from France and other Western European countries. I. morrisoni (Swain), known to live on numerous conifers, can be frequently found on Cupressaceae and particularly on Cupressus arizonica, on which it has been observed in France. Unlike the former species, I. liriodendri (Monell) is monophagous on the tuliptree, Liriodendron tulipifera (Magnoliaceae), which is an urban as well as a forest tree of interest in the area. Some morphological characters which are useful for the identification of the two species are illustrated and elements concerning their biology in the newly colonized area are discussed.
Keywords: Illinoia liriodendri; Illinoia morrisoni; new records; France; Italy